Finance and Development, March 2004. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2004)
This paper presents a snapshot of changes in the world's health and demographic conditions. The paper highlights that in most parts of the world, individuals are healthier and living longer, thanks to improved health services and living conditions and the more widespread use of immunization, antibiotics, and better contraceptives. Although this trend is likely to continue, hopes are fading in some regions where progress slowed or stopped in the 1990s, primarily as a result of the AIDS epidemic. Moreover, most regions of the developing world will not reach the Millennium Development Goals for health by 2015.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet